Alkali and rare earth metals loading on deoiled-spent bleaching clay as catalysts in transesterification of waste oils - Rehan, Zainol Abidin (2017)
In the present work, waste source, namely deoiled spent bleaching clay (DSBC) loaded with K, Ca and La, have been successfully utilized as solid catalysts in the transesterification of refined, bleached and deodorized palm olein (RBD-PO), waste palm cooking oil (WPCO) and spent bleaching clay (SBC) oil to produce methyl esters (biodiesel). The triglycerides source from waste source such as WPCO and SBC can help to reduce the production cost and do not cause food issue. But these types of feedstocks have high moisture and free fatty acid (FFA) hence; we need to find a heterogeneous catalyst to overcome this. In order to enhance the catalytic activity, the deoiled SBC had been calcined at 500 °C for 10 h and doped with KOH, CaO and La2O3 using wet impregnation method. The catalysts were characterized with TGA, FTIR, XRD, XRF, BET, FESEM, ICP and Hammett indicators (phenolphthalein, 2,4-dinitroaniline and 4-nitroaniline). In the transesterification reaction, we found out that K-DSB gives the best yield. The best reaction conditions found to be: for transesterification of RBD-PO, WPCO and SBC oil using K-DSBC was 3 wt.% catalyst amount (based on oil weight) and 9:1 methanol to oil molar ratio for 2 h reaction period producing 98.9 % methyl ester yield. Meanwhile for the transesterification of WPCO and SBC oil require 3 h and 4 h reaction duration. All catalysts undergo transesterification at the reflux temperature of methanol (65 °C). Furthermore, the regenerated of the catalytic activity was investigated, and found that all the three catalysts could be reused up to five times, while maintaining methyl esters content above 80%. In addition, the catalysts exhibit tolerance towards the presence of water at 1.75% and 2.0% and FFA at 1.75% and 1.75%, respectively, with over 80% of methyl esters content.